2015
DOI: 10.1111/resp.12486
|View full text |Cite|
|
Sign up to set email alerts
|

Tc17 cells are associated with cigarette smoke‐induced lung inflammation and emphysema

Abstract: Background and objective: Some types of T lymphocytes, especially cytotoxic T-cells (Tc1) and T-helper (Th17) cells, play a pivotal role in cigarette smokeinduced lung diseases. However, whether Tc17 cells are involved remains largely unknown.We investigated Tc17 involvement using a cigarette smoke-exposure model. Methods: Groups of mice were exposed to cigarette smoke or filtered air. At weeks 2, 8, 12 and 24, mice were sacrificed to observe histological changes by HE stain and/or immunohistochemical staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
(46 reference statements)
1
26
1
Order By: Relevance
“…It has been shown that the numbers of Tc17 cells in the lung were increased in patients with COPD (11). Zhou et al reported that long-term cigarette smoke exposure induced Tc17 cell expansion(44). In the present study, IL-17A + CD8 + T cells in the lungs of control-IgG treated mice tended to be increased following PPE instillation, but treatment with anti-IL-23p40 did not affect the numbers of these T cells.…”
contrasting
confidence: 50%
“…It has been shown that the numbers of Tc17 cells in the lung were increased in patients with COPD (11). Zhou et al reported that long-term cigarette smoke exposure induced Tc17 cell expansion(44). In the present study, IL-17A + CD8 + T cells in the lungs of control-IgG treated mice tended to be increased following PPE instillation, but treatment with anti-IL-23p40 did not affect the numbers of these T cells.…”
contrasting
confidence: 50%
“…A study on BAL from mice, which were exposed to tobacco smoke for at least six months, showed that the number of Th1 and Th17 cells was significantly elevated [31]. Mice with emphysema had an increased expression of Th1-type cytokine IFN-γ and Th17-type IL-17A [32, 33] and/or augmented numbers of Th17/Tc17 and Tc1 cells [33, 34]. Therefore, both murine experiments and human studies suggest that increases in Th1 and Th17 cell subsets are associated with pulmonary inflammation as a result of cigarette smoke exposure (CSE).…”
Section: Effects Of Cigarette Smoking On Adaptive Immunitymentioning
confidence: 99%
“…Cigarette smoke-induced pulmonary inflammation, such as chronic obstructive pulmonary disease (COPD), is the fourth leading cause of death worldwide [ 1 3 ]. Many lines of evidence indicate that adaptive immunity plays important roles in the development of COPD, and the systemic inflammation may be a result of overspill of inflammatory mediators from the lungs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%